Regenerative therapies in neonatology: clinical perspectives - Gortner, Ludwig; Bieback, Karen; Klüter, Harald (Klinische Pädiatrie, 2012)
Regenerative therapy based on stem cells is applied as standard therapy in pediatric oncology. Furthermore, they are frequently used to treat immunodeficiency disorders of infants. For severe neonatal diseases, e. g. hypoxic-ischemic encephalopathy in term neonates or bronchopulmonary dysplasia in preterm infants, animal models have been established. According to some first preclinical results stem cell administration appears as a promising tool to improve the clinical outcome in high-risk infants. Provided the benefit of regenerative therapies can further be evaluated in appropriate preclinical neonate models, carefully controlled clinical trials to assess the significance of regenerative therapies, such as autologous stem cell administration, are indicated.